2005
DOI: 10.1111/j.1365-2583.2005.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

20‐Hydroxyecdysone indirectly regulates Hemolin gene expression in Hyalophora cecropia

Abstract: Development and innate immune defence are two vital processes that have been demonstrated to use the same or similar molecules and signalling pathways in insects. Hemolin is a moth haemolymph protein belonging to the immunoglobulin superfamily. It is strongly induced upon bacterial infection. However, recent studies indicate a developmental regulation of hemolin. We show that the steroid hormone 20-hydroxyecdysone (20E) can activate the expression of Hyalophora cecropia Hemolin (HcHemolin) in the fat body of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Due to its adhesion properties, some hemolins have been involved in the cell adhesion mechanism (37). Some studies reveal that hemolins are present in neural tissues in several phases of embryonic development (24), and their expression correlates with hormones that regulate moulting and metamorphosis of lepidopters (19,45). It seems clear that hemolins are multifunctional proteins with roles in defense (cellular and humoral) and in development (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its adhesion properties, some hemolins have been involved in the cell adhesion mechanism (37). Some studies reveal that hemolins are present in neural tissues in several phases of embryonic development (24), and their expression correlates with hormones that regulate moulting and metamorphosis of lepidopters (19,45). It seems clear that hemolins are multifunctional proteins with roles in defense (cellular and humoral) and in development (22).…”
Section: Discussionmentioning
confidence: 99%
“…Hemolin is a bacteria-inducible immunoglobulinlike protein whose role in insect immunity has been better studied. In the last 2 decades, independent studies have demonstrated that hemolin proteins are multifunctional molecules involved in a diverse range of cell interaction and are able to (a) bind lipopolysaccharides and be up-regulated in hemolymph during infections (15)(16)(17); (b) be up-regulated during metamorphosis (18,19); (c) promote opsonin-like effects, such as increased cell adhesion and phagocytosis (20,21); (d) agglutinate bacterial cells (17,22); (e) bind to hemocytes and inhibit their aggregation (15,20,22,23); and (f) regulate embryonic development (24,25).…”
mentioning
confidence: 99%
“…Hemolins are bacteria-induced proteins sharing homology with neural cell adhesion molecules [3]. Of note, they are also highly expressed in the caterpillars’ epidermis, but, due to their adhesion properties, they have been related to the immune system processes [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Dunn and co-workers consider the possibility that cells of the midgut epithelium release lysozyme into the lumen of the midgut and into the hemolymph at the prepupal stage (Dunn et al, 1994). As increasing levels in hemolymph are also described for other immune relevant proteins, it has been suggested that these higher levels counter bacterial activity during the vulnerable period of midgut remodeling associated with metamorphosis (Samakovlis et al, 1990;Tryselius et al,1992;Daffre et al, 1994).In addition, a number of recent reports show evidence that the expression pattern of immune relevant proteins are governed by changing ecdysteroid titers (Meister and Richards, 1996;Ahmed et al, 1999;Roxstrom-Lindquist et al, 2005). …”
mentioning
confidence: 97%